Line scan of sediment core PHE1 retrieved from the Pheneos Polje (Peloponnese, Greece) - Joana Seguin; Pavlos Avramidis; Annette Haug; Torben Kessler; Arndt Schimmelmann; Ingmar Unkel (PANGAEA, 2020)
The sediment core PHE1 (37.85114° N, 22.33510° E) was retrieved from the eastern bay of the Pheneos Polje, Peloponnese Greece, in spring 2017 using a piston corer (Stitz type). The sedimentary sequence covers 390 cm (sedimentary units 1 - 9). RGB colour values were taken with a digital line scan camera to depict colour variation with depth. The core sequence covers the largest part of the Holocene and was analysed to reconstruct ecosystem and landscape changes as well as palaeoclimatic fluctuations in southern Greece.
In: Seguin, J et al. (2020): Geochemical and sedimentological record of sediment core PHE1 retrieved from the Pheneos Polje (Peloponnese, Greece) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.921424